1969
DOI: 10.1161/01.cir.39.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Corrected Transposition of the Great Vessels in a 73-Year-Old Man

Abstract: SUMMARYThe case of a 73-year-old white man with corrected transposition of the great vessels and associated mitral and mild aortic regurgitation is reported. The patient's survival was the longest of any patient with this defect reported to date. Although the condition is theoretically compatible with a normal life span, few patients with this lesion survive past 40 years of age because of associated congenital defects or the subsequent development of A-V valvular insufficiency or heart block, or both. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

1985
1985
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…It is known that atrioventricular discordance (also called corrected transposition) may be compatible with a normal life span when there is no other significant abnormality [1,7] . However, congenital cardiac defects associated with atrioventricular discordance affect the clinical presentation and outcome [2,4] .…”
mentioning
confidence: 99%
“…It is known that atrioventricular discordance (also called corrected transposition) may be compatible with a normal life span when there is no other significant abnormality [1,7] . However, congenital cardiac defects associated with atrioventricular discordance affect the clinical presentation and outcome [2,4] .…”
mentioning
confidence: 99%
“…Congenitally corrected transposition of the great arteries is a rare cardiac malformation which has a unique pathology as well as variable clinical presentation even in the seventh decade of life . The natural history and clinical presentation of the cases with cc‐TGA are closely related to the coexistence of a ventricular septal defect, which is reported to be the most commonly associated congenital heart defect in these patients .…”
Section: Discussionmentioning
confidence: 99%
“…Pathologic reviews at autopsy of patients with ccTGA revealed systemic AV valve anomalies in 91-97% of cases and a VSD in 78%. 3,4 Though some patients without associated anomalies may not be diagnosed until later in life, [5][6][7] patients with ccTGA often present in infancy or childhood with symptoms of congestive heart failure secondary to a VSD. 8 Surgical planning for patients with ccTGA is related to the presence of a VSD, pulmonary stenosis, and the state of the right ventricle.…”
Section: Discussionmentioning
confidence: 99%